#TITLE_ALTERNATIVE# - FADHILA (NIM 15107007); Pembimbing: Dr. Ir. Dina Anggreni, M.T., dan Irwan Gumilar, S.T, M.si., HANNA
West Java is one of the regions in Indonesia that has the potential to be devastating earthquake, this can be seen from the position subduction zone in the West Java area of the Eurasian plate and the Indo-Australian plate. At present it has formed three active faults in West Java, including Cimandiri fault, Lembang fault, and Baribis fault. Baribis fault is active faults with the most recent formation of the fault lines stretching from Subang to the hilly terrain around Mount Ciremai. Baribis fault has considerable potential to be an earthquake, and therefore required monitoring activity on Baribis fault. One method that can be applied to monitor the activity of Baribis fault is to use a GPS survey methods. GPS observational data were processed using the scientific software Bernese 5.0 then used to calculate the value of the shift vector, the strain, and slip rate for deformation analysis. Based on the analysis of the deformation,it is known that fault activity occurred in the Baribis fault. Data processing results show that the vector shift in Baribis fault leads to the north-west by the shift in the range of 2 mm/year up to 5 cm / year. Based on the pattern of strain, in Baribis fault suffered equally extension and compression, but compression values tend to be larger than the value of the extension. The estimated slip rate of this fault has a value of 1.9 cm/ year.